2006
DOI: 10.1038/sj.onc.1210070
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of TMPRSS2-ERG fusion transcripts in the human prostate

Abstract: TMPRSS2-ERG gene fusions have recently been reported to be present in a high proportion of human prostate cancers. In the current study, we show that great diversity exists in the precise structure of TMPRSS2-ERG hybrid transcripts found in human prostates. Fourteen distinct hybrid transcripts are characterized, each containing different combinations of sequences from the TMPRSS2 and ERG genes. The transcripts include two that are predicted to encode a normal full-length ERG protein, six that encode N-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

24
208
3
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(242 citation statements)
references
References 12 publications
(20 reference statements)
24
208
3
6
Order By: Relevance
“…Several studies have consistently confirmed that fusion at exon 1 of TMPRSS2 is the most common variant (Tu et al, 1996;Wang et al, 2006;Clark et al, 2007). However, Clark et al (2007) also found that distinct patterns of hybrid transcripts from separate areas of the same tumour which would make associations of clinical significance more difficult. These and other separate fusion transcripts will require further study to examine for their association with prostate cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have consistently confirmed that fusion at exon 1 of TMPRSS2 is the most common variant (Tu et al, 1996;Wang et al, 2006;Clark et al, 2007). However, Clark et al (2007) also found that distinct patterns of hybrid transcripts from separate areas of the same tumour which would make associations of clinical significance more difficult. These and other separate fusion transcripts will require further study to examine for their association with prostate cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many other rare transcripts of this gene fusion have been described (Soller et al, 2006;Wang et al, 2006;Clark et al, 2007;Liu et al, 2007;Tu et al, 2007). We only examined the most common fusions of TMPRSS2 exon 1 with exon 4 of ERG transcript.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 In prostate cancer, multiple TMPRSS2-ERG fusion variants have been identified at the transcript level, most of them involving only the 5 0 untranslated sequence of TMPRSS2. 6,[12][13][14][15] The TMPRSS2-ETS fusions thus lead to overexpression of the ERG or ETV protein induced by the TMPRSS2 promoter. In contrast to other translocations involving the ERG gene, for example, EWS-ERG fusion, no fusion protein is expected in most TMPRSS2-ERG fusions.…”
mentioning
confidence: 99%